Association of Selenium Intake and Development of Depression in Brazilian Farmers - Ferreira de Almeida, Tatiana Lourençoni; Petarli, Glenda Blaser; Cattafesta, Monica; Zandonade, Eliana; Bezerra, Olivia Maria de Paula Alves; Tristão, Kelly Guimães; Salaroli, Luciane Bresciani (Frontiers in Nutrition, 2021)
Introduction: Depression and deficiency in the consumption of micronutrients are a public health problem, especially in the rural population. The deficiency in selenium consumption affects mental health, contributing to the development of major depressive disorders. Thus, this study aimed to evaluate selenium intake and its association with depressive symptoms in farmers in southeastern Brazil. Material and Methods: Epidemiological, cross-sectional, and analytical study with 736 farmers aged between 18 and 59. A semistructured questionnaire was used to collect sociodemographic, lifestyle and clinical condition data. For evaluation of food intake, three 24-hour recalls were applied, and for identification of depressive episodes, the Mini-International Neuropsychiatric Interview was conducted. Results: A total of 16.1% (n = 119) of the farmers presented symptoms of major depressive episodes, 5.8% (n = 43) presented symptoms of current depressive episodes, and 10.3% (n = 76) presented symptoms of recurrent major depressive episodes. Sociodemographic factors associated with depression were gender (p < 0.001), marital status (p = 0.004), and socioeconomic class (p = 0.015). The consumption of high doses of selenium was associated with a reduction of approximately 54% in the chances of occurrence of depression (OR = 0.461; 95% CI = 0.236-0.901). Conclusion: High selenium intake is associated with a lower prevalence of depression even after adjusting for sociodemographic variables, lifestyle, and pesticide intoxication. The findings of this study contributed to highlighting the high prevalence of depression in rural areas and its relationship with selenium intake.